A novel Fe(II)/citrate/UV/peroxymonosulfate process for micropollutant degradation: Optimization by response surface methodology and effects of water matrices. (October 2017) - Ling, Li; Zhang, Dapeng; Fang, Jingyun; Fan, Chihhao; Shang, Chii
Abstract: This paper applied the response surface methodology (RSM) to optimizing a novel Fe(II)/citrate/UV/PMS process in the degradation of a model micropollutant, carbamazepine (CBZ), a persistent emerging contaminant frequently detected in surface water and groundwater. The experimental conditions in terms of two responses, CBZ removal efficiency (Y1) and cost per unit CBZ removal (Y2), were optimized by the central composite design (CCD) in RSM. Modeling data exhibited that the optimum condition resulting in the lowest Y2 while achieving >70% of Y1 was at a UV dose of 265.5 mJ/cm 2 and Fe(II), PMS and citrate concentrations of 12.2 μM, 100 μM and 26.4 μM, respectively. Increasing Fe(II) concentration led to the decrease in CBZ degradation and cost-effectiveness of the process. On the other hand, increasing the UV dose, PMS concentration and citrate/Fe(II) ratio over 265.5 mJ/cm 2, 100 μM and 2.16:1, respectively, slightly increased the CBZ degradation, but significantly increased the cost. Under the optimized condition, the experimentally obtained values for Y1 and Y2 were 70.44% and 0.0104 H K$/%/m 3, respectively. The predicted Y1 and Y2 were 71.07% and 0.0098 H K$/%/m 3, respectively, suggesting that RSM can be readily used to determine the optimum condition of the Fe(II)/citrate/UV/PMS process for CBZ degradation. Other aqueous constituents which impacted the CBZ removal in the Fe(II)/citrate/UV/PMS process are in the following order: NOM > alkalinity > bromide > ammonia ≈ chloride (both negligible). Graphical abstract: Highlights: The degradation of CBZ by Fe(II)/citrate/UV/PMS process was optimized by RSM. The predicted results by RSM matched well with the experimental observation. The optimum case was 265.5 mJ/cm 2 UV, 100 μM PMS, 12.2 μM Fe(II), and 26.4 μM citrate. The process requires low Fe(II) and citrate doses and works well at neutral pH. The water matrix impacts exhibited: NOM > alkalinity > bromide > ammonia = chloride.